Young Children and Adults Show Differential Arousal to Moral and Conventional Transgressions - Yucel, Meltem; Hepach, Robert; Vaish, Amrisha (Frontiers in Psychology, 2020)
From a young age, children understand and enforce moral norms, which are aimed at preserving the rights and welfare of others. Children also distinguish moral norms from other types of norms such as conventional norms, which serve to ensure coordination within social groups or institutions. However, far less is known about the mechanisms driving this differentiation. This paper investigates the role of internal arousal in distinguishing moral from conventional norms. In a between-subjects design, 3-year-olds (n = 32), 4-year-olds (n = 34), and undergraduate students (n = 64) watched a video of either a moral norm violation (e.g., destroying another person’s artwork) or a conventional norm violation (e.g., playing a game wrong). Participants of all age groups showed differential physiological arousal (pupil dilation) to moral and conventional norm violations. Participants of all age groups also attended significantly more to the victim of the moral transgression than the bystander in the conventional transgression. Further, this differential attention to the victim/bystander positively correlated with the change in participants’ phasic pupil dilation to the norm violation. This is the first evidence that differences in internal arousal co-occur with (and possibly contribute to) the distinction that even young children draw between moral and conventional norms.